Long Neural Genes Harbor Recurrent DNA Break Clusters in Neural Stem/Progenitor Cells - Wei, Pei-Chi (Cell, 2016)
Repair of DNA double-strand breaks (DSBs) by non-homologous end-joining is critical for neural development, and brain cells frequently contain somatic genomic variations that might involve DSB intermediates. We now use an unbiased, high-throughput approach to identify genomic regions harboring recurrent DSBs in primary neural stem/progenitor cells (NSPCs). We identify 27 recurrent DSB clusters (RDCs) and, remarkably, all occur within gene bodies. Most of these NSPC RDCs were detected only upon mild, aphidicolin-induced replication stress, providing a nucleotide-resolution view of replication-associated genomic fragile sites. The vast majority of RDCs occur in long, transcribed, and late-replicating genes. Moreover, almost 90% of identified RDC-containing genes are involved in synapse function and/or neural cell adhesion, with a substantial fraction also implicated in tumor suppression and/or mental disorders. Our characterization of NSPC RDCs reveals a basis of gene fragility and suggests potential impacts of DNA breaks on neurodevelopment and neural functions.